Pengembangan Modal Masyarakat Melalui Penerapan Akad Syariah oleh Kopontren Sidogiri pada Toko Basmalah Sidogiri Pasuruan - Sulastri, Sulastri; Faizah, Faizah (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
Cooperatives serve as a strategic solution for low-income communities in addressing economic challenges, including in Islamic boarding schools (pesantren), which develop Sharia-based cooperatives known as Kopontren. Proper capital management aligned with Sharia principles is essential to ensure business sustainability and to prevent involvement in usury-based practices that remain prevalent in financial activities. This study aims to: (1) examine the capital collection process in Kopontren Sidogiri, (2) identify the Sharia contracts used in the capital collection, and (3) analyze capital development strategies implemented in Toko Basmalah of Sidogiri Islamic Boarding School Pasuruan. The research employed a descriptive qualitative approach using interviews, observations, and documentation. The results reveal that Kopontren Sidogiri initially collected capital from family contributions and teachers, and later expanded by opening membership to the surrounding community. Three Sharia contracts were applied: ijarah, musyarakah, and mudharabah, all supervised by an internal Sharia supervisory board. Capital development is carried out through business strategy optimization and the establishment of several subsidiary units to strengthen Kopontren Sidogiri’s economic growth.